Means-Tested Solar Subsidies - Mark Colas; Emmett Reynier (CESifo GmbH, 2024)
We study the optimal design of income-contingent subsidies for residential solar panels. Using remotely sensed data on solar panel installations across the contiguous US and a border-discontinuity design, we estimate that the responsiveness of installation rates to subsidies is strongly decreasing in income. Using these empirical elasticities, we estimate a model that embeds a solar panel installation decision into a dynamic consumption/savings framework with borrow-ing constraints. Counterfactual simulations reveal that switching to production-maximizing income-contingent subsidies leads to a three-fold increase in public funds received by low-income households and a 2.4% increase in national solar production. Means-tested subsidies are justified on both equity and efficiency grounds.
Keywords: H21; H23; Q42; Q48; 330; rooftop solar; subsidies; renewable energy